Preparation and microstructural analysis of poly(ethylene oxide) comb‐type grafted poly(N‐isopropyl acrylamide) hydrogels crosslinked by poly(ϵ‐caprolactone). Issue 1 (27th June 2012) - Miao, Lei; Lu, Mangeng; Yang, Chaolong; Zhang, Yunfei; Shen, Tengfei; Ma, Jianying
Abstract Poly(N‐isopropyl acrylamide) (PNIPAAm)‐graft‐poly(ethylene oxide) (PEO) hydrogels crosslinked by poly(ϵ‐caprolactone) diacrylate were prepared, and their microstructures were investigated. The swelling/deswelling kinetics and compression strength were measured. The relationship between the structure and properties of hydrogel are discussed. It was found that the PEO comb‐type grafted structure reduced the thermosensitivity and increased the compression strength. The addition of poly(ϵ‐caprolactone) (PCL) accelerated the deswelling rate of the hydrogels. Meanwhile, the entanglement of PCL chains restrained the further swelling of the network of gels. The PCL crosslinking agent and PEO comb‐type grafted structure made the behavior of the hydrogels deviate from the rubber elasticity equations. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013